Involvement in Higgs Domino Island and Its Perceived Behavioral Implications in Gampong Lamdingin, Banda Aceh - Asmanidar Asmanidar (Sinthop: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2026)
Digital games that incorporate betting mechanisms and allow virtual chips to be exchanged for money may develop from recreational activities into forms of online gambling. This study examines the factors associated with residents’ involvement in Higgs Domino Island and the perceived implications of such involvement for religious routines, social relations, education, productivity, and economic management in Gampong Lamdingin, Banda Aceh. The study employed a descriptive qualitative case-study design. Data were collected through semi-structured interviews, observation, and documentation involving 13 purposively selected informants consisting of players and individuals who interacted closely with them. The data were analyzed through repeated familiarization, coding, thematic grouping, comparison across accounts, and interpretive synthesis. Credibility was strengthened by comparing information across informants and data-collection techniques. The findings indicate three recurring pathways of involvement: peer and environmental exposure, repeated play that became increasingly difficult to control, and expectations of rapid economic gain. Some informants also described a gap between awareness of the religious prohibition of gambling and effective behavioral restraint. Reported implications included delayed worship, disrupted sleep and productivity, interpersonal discomfort or conflict, borrowing money or requesting salary advances to purchase chips, and reduced attention to educational activities. The intensity and form of these implications varied across cases. The study does not establish causal effects or clinical diagnoses; rather, it presents context-specific accounts of involvement and perceived behavioral change. The findings suggest that prevention should combine digital and financial literacy, family and peer support, contextual religious education, restrictions on chip-related financing, and access to appropriate counseling.